Investigation of length heteroplasmy in mitochondrial DNA control region by massively parallel sequencing. (September 2017) - Lin, Chun-Yen; Tsai, Li-Chin; Hsieh, Hsing-Mei; Huang, Chia-Hung; Yu, Yu-Jen; Tseng, Bill; Linacre, Adrian; Lee, James Chun-I
Highlights: Accurate decoding of mitochondrial hypervariable regions can be problematic due to variable numbers of cytosines in poly C stretches. Comparison of data is provided generated by Sanger sequencing and massively parallel sequencing for HVI, HVII and HVII. Varying designations of bases occurred depending on the software used. Applying the program SEQ Mapper to MPS data gave the most reliable results and reported the greatest number of variants. Abstract: Accurate sequencing of the control region of the mitochondrial genome is notoriously difficult due to the presence of polycytosine bases, termed C-tracts. The precise number of bases that constitute a C-tract and the bases beyond the poly cytosines may not be accurately defined when analyzing Sanger sequencing data separated by capillary electrophoresis. Massively parallel sequencing has the potential to resolve such poor definition and provides the opportunity to discover variants due to length heteroplasmy. In this study, the control region of mitochondrial genomes from 20 samples was sequenced using both standard Sanger methods with separation by capillary electrophoresis and also using massively parallel DNA sequencing technology. After comparison of the two sets of generated sequence, with the exception of the C-tracts where length heteroplasmy was observed, all sequences were concordant. Sequences of three segments 16184–16193, 303–315 and 568–573 with C-tracts in HVI, II and III can be clearly defined from the massively parallel sequencing data using the program SEQ Mapper. Multiple sequence variants were observed in the length of C-tracts longer than 7 bases. Our report illustrates the accurate designation of all the length variants leading to heteroplasmy in the control region of the mitochondrial genome that can be determined by SEQ Mapper based on data generated by massively parallel DNA sequencing.